Review Optimasi Ukuran dan Ketebalan Pizoelektrik untuk Pemanenan Energi Hujan pada Atap Model Bangunan sebagai Sumber Energi Listrik - Kurnia Sandi Oktaris; Rifky (Prosiding Seminar Nasional Teknoka, 2025)
This This study aims to examine the optimization of the size and thickness of piezoelectric as the main element in harvesting rain energy from raindrops. The method used is an experiment by varying the size of the piezoelectric (1x1 cm, 3x3 cm, 5x5 cm) and thickness (0.2-0.5 cm) which is installed on the roof of the building model. The research variables measured are voltage and electric current using a multitester three times for data validity. The data is processed to determine the output electrical power and efficiency of the piezoelectric energy conversion system. The results of the study and experiments show that the size and thickness of the piezoelectric affect the output electrical power and efficiency. The results of this study found that the optimal dimensions of the piezoelectric determine the maximum output electrical power and efficiency.